ANALISIS KESUKSESAN SISTEM INFORMASI SIBUBA DALAM PENCATATAN DAN PELAPORAN P4K KABUPATEN BONDOWOSO - Vindiarta Ansori, Fara; Khoiri, Abu; Sandra, Christyana (Universitas Islam Negeri Alauddin Makassar, 2024)
The childbirth planning and complication prevention (P4K) program is one of the efforts to reduce MMR and IMR. One activities of P4K is to record and report on mothers and babies. In 2019, Bondowoso district published a maternal and infant recording and reporting application called SIBUBA. During its use, the SIBUBA application experienced errors when officers entered data but the data did not appear in the system. This study aims to analyze the factors related to the success of the SIBUBA information system in supporting the recording and reporting of the P4K program in Bondowoso district. This research is an analytic study with a cross sectional design. The research is conducted in 5 health center areas selected by cluster sampling with a total sample of 52 respondents. Data analysis is conducted with logistic regression test. The results showed that system quality (p = 1.182), information quality (p = 0.629), service quality (p = 0.551) have no effect on usage. System quality (p = 0.017), information quality (p = 0.003), service quality (p = 0.011) affect user satisfaction. The usage (p = 0.222) has no effect on net benefits. User satisfaction (p=0.001) affects net benefits.